SYSTEMATIC EDUCATION AND INTELLECTUAL CULTURAL FORMATION MECHANISMS - Ж. Рўзиев (Web of Journals Publishing, 2023)
The main objective of the state policy in this article is to increase the convenience and quality of education, to respond to the needs of the society and its every citizen, and to improve the quality of education. Social-philosophical analysis of the mechanisms that shape intellectual culture.
Keywords: education, educational philosophy, creativity, creative thinking, science, methodological consciousness, object, mind, innovation, constructivism, worldview.